Retinal Microvascular Reactivity in Chronic Cigarette Smokers and Non-smokers: An Observational Cross-Sectional Study - Xu, Huan; Zong, Yuan; Yu, Jian; Jiang, Chunhui; Zhu, Haohao; Sun, Xinghuai (Frontiers in Medicine, 2021)
Purpose: To evaluate the changes in the retinal microvasculature and its reactivity in chronic cigarette smokers. Methods: Thirty-four male chronic cigarette smokers and 18 male nonsmokers were enrolled. Optical coherence tomography angiography was used to measure the perfused retinal vessel densities (PVDs) of the parafoveal and peripapillary areas at baseline and during phase IV of the Valsalva maneuver (VM-IV). Systemic blood pressure and intraocular pressure were also measured. Results: The baseline PVD in the peripapillary area was significantly lower in the smokers than in the nonsmokers (59.56% ± 2.26% vs 61.67% ± 3.58%, respectively; P = 0.005). However, there were no significant differences in the foveal avascular zone or parafoveal PVD between the two groups. During VM-IV, the parafoveal PVD of the smokers decreased by 5.49% ± 9.70%, which was significantly less than the percentage change in the nonsmokers (-13.01% ± 8.39%, P < 0.05). Similarly, the peripapillary PVD of the smokers decreased by 1.13% ± 3.50%, which was significantly less than that in the nonsmokers (-3.83% ± 4.26%, P < 0.05). There were no significant differences in the percentage changes in systemic blood pressure parameters between the two groups. Conclusion: The retinal microvasculature and its reactivity were impaired in chronic smokers compared with nonsmokers. The extent of impairment differed among different regions of the fundus.